Modelling Alternative Energy in the Electricity Market - Pereira Simoes Matos, G (Oxford University;Mathematical Institute, 2013)
In this thesis, we try to analyse the consequences to the electricity market when we try to introduce wind farms. We start by following [1], considering a large number of fuel-fired power plants bidding according to a Ornstein-Uhlenbeck process and building a bid-stack curve from these. To introduce wind power generation, we model the wind speed at each location by a similar process and extract the total power generated by wind farms from it. We then consider the implications this power has on the bid-stack curve, and we try to anticipate how the market might evolve and adapt.